Improving integrated thematic learning outcomes using the numbered head together (NHT) cooperative mode - Fadhila Aulia; Mai Sri Lena (Universitas Negeri Yogyakarta, 2023)
This study used a classroom action research method by applying qualitative and quantitative approaches carried out in 2 cycles through the stages of planning, implementation, observation, and reflection. This study aimed to observe the improvement of student learning outcomes in class VB SDN 13 Kuranji by applying the Numbered Head Together (NHT) Model. The research data obtained were analyzed using qualitative and quantitative techniques with the instruments of the Teaching Implementation Plan (RPP) assessment sheet, teacher and learner activity observation sheets, evaluation question sheets, attitude journals, and skill rubrics. Teachers and students became the subjects of this study. According to the results of the study, there was an increase in each cycle. In the lesson plan assessment in Cycle I, the score was 85%, and 95% in Cycle II. Regarding teacher activity, the value reached 84.3% in Cycle I and 93.7% in Cycle II, while the learner aspect in Cycle I was 82.8% to 93.7% in Cycle II. In addition, students' learning outcomes increased from 78.4 in Cycle I to 87 in Cycle II. The results showed improved student learning outcomes after applying the Numbered Head Together model. The improvement is also seen in the lesson plan and the implementation of learning regarding teachers and students.